The underlying mechanisms of oxytetracycline degradation mediated by gut microbial proteins and metabolites in Hermetia illucens - Cao, Qingcheng; Liu, Cuncheng; Li, Yun; Qin, Yuanhang; Wang, Cunwen; Wang, Tielin (The Science of the total environment, 2024)
Hermetia illucens larvae can enhance the degradation of oxytetracycline (OTC) through its biotransformation. However, the underlying mechanisms mediated by gut metabolites and proteins are unclear. To gain further insights, the kinetics of OTC degradation, the functional structures of gut bacterial communities, proteins, and metabolites were investigated. An availability-adjusted first-order model effectively evaluated OTC degradation kinetics, with degradation half-lives of 4.18 and 21.71 days for OTC degradation with and without larval biotransformation, respectively. Dominant bacteria in the larval guts were Enterococcus, Psychrobacter, Providencia, Myroides, Enterobacteriaceae, and Lactobacillales. OTC exposure led to significant differential expression of proteins, with functional classification revealing involvement in digestion, transformation, and adaptability to environmental stress. Upregulated proteins, such as aromatic ring hydroxylase, acted as oxidoreductases modifying the chemical structure of OTC. Unique metabolites, aclarubicin and sancycline identified were possible OTC metabolic intermediates. Correlation analysis revealed significant interdependence between gut bacteria, metabolites, and proteins. These findings reveal a synergistic mechanism involving gut microbial metabolism and enzyme structure that drives the rapid degradation of OTC and facilitates the engineering applications of bioremediation. [Display omitted] •Hermetia illucens gut functional structures driving the rapid degradation of OTC.•Larval gut microbiota had enough functional redundancy to tolerate OTC stress.•Gut bacterial proteases modified and led the degradation of OTC.•Tetracycline derivatives, aclarubicin and sancycline were detected.